MITIGATION OF SOLAR CELL HEAT BY USING SUNSCREEN FILM - Siagian, Parlin; Hamdani, Hamdani; Dalimunthe, M. Erpandi (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Solar power plants (PLTS) generate electricity from solar cells that are exposed to sunlight. The high and low voltage produced is dependent on the amount of sunlight that hits the solar cell panel. The intensity of exposure to sunlight that is too high will cause heat in the solar cell panels. Excessive heat above 50C will have an impact on decreasing the ability of solar cell panels. Previous studies have discussed a lot about the effect of sunlight that is too high to reduce the ability of solar cell panels. Solar cell cooling techniques have been discussed in previous studies. This research was made to mitigate excessive heat in solar cell panels. The technique used is to reduce the intensity of sunlight hitting the panel by coating the top that receives sunlight with sunscreen. With this layer, excess solar heat in the solar cell will be partially reflected into the air. The sunscreen filter will lower the output voltage of the solar panel because the sun's energy reaching the surface of the panel is reduced. The voltage drop generated by solar panels occurs because of the presence of a screen that reduces the lumen of light that penetrates the sunscreen.